Successful renal transplantation in a patient with a Wiskott-Aldrich syndrome protein (WASP) gene mutation - Chovancová, Zita; Kuman, Milan; Vlkova, Marcela; Litzman, Jiri (Transplant international, 2015)
Wiskott-Aldrich syndrome (WAS) is a rare primary immunodeficiency disorder caused by mutations in the WAS protein (WASP) gene. Renal disease progressing to renal failure is a well-recognized complication in patients with WAS. Only a few case reports of renal transplantation have been reported to date. Here, we present a patient with a WASP mutation who suffered from severe atopic eczema, mild thrombocytopenia and only a slightly increased frequency of infections, who then developed IgA nephropathy and consequently underwent renal transplantation, which was successful. This study demonstrates that renal transplantation is possible in patients with WAS, regardless of conceivable complications.
Keywords: Glomerulonephritis, IGA; Kidney Transplantation; genetické markery; mužské pohlaví; Wiskott-Aldrich Syndrome; mutace; Wiskottův-Aldrichův syndrom; Wiskott-Aldrich Syndrome Protein; lidé; IgA nefropatie; Mutation; Humans; transplantace ledvin; Genetic Markers; mladiství; Male; Adolescent; protein Wiskottova-Aldrichova syndromu